Effectiveness Network Governance In Making of Special Regional Regulations In Papua Province - Bonso, Hamjah; Suranto, Suranto (Journal of Governance and Public Policy, 2018)
Abstract-Since the implementation of Special Autonomy law, the system of governance of Papua province experiencing changes in terms namely institutional establishment of the Papuan People's Assembly (MRP). The presence of MRP institutions greatly affect the implementation of the Provincial Government of Papua, especially in the manufacture of specific local regulations. The purpose of this study was to determine the effectiveness of the network between local governance institutions in the manufacture of specific local regulations (Perdasus) in Papua province. This study uses "triangulation" that combines qualitative and quantitative methods. The use of this method to produce a general overview of the phenomenon to be studied. In this study suggest that the making of specific local regulations (Perdasus) involving the three institutions namely the provincial government, the DPRP and MRP have done quite effectively. It is characterized by involvement, commitment, roles, and the implementation of mechanisms of each institution towards making Perdasus based authority. The study recommends that the need for institutional capacity development, especially against the MRP as a representative institution of the Papuan people.